Impact of Foreign Employment on Entrepreneurial Activities in Pokhara Metropolitan City - Thapa, Kiran (Kalika Journal of Multidisciplinary Studies, 2024)
This research investigates the influence of foreign employment on the business establishment in the home countries of labour migrants through mediating roles of increased income, skill acquisition, and experience, within the context of entrepreneurial economics. Employing a descriptive and analytical research design, the study utilises primary quantitative data to analyse the relationships among these variables rigorously. The findings demonstrate that experience and skills acquired abroad significantly influence the likelihood of business establishment upon return. In contrast, the anticipated positive effects of increased earnings resulting from foreign employment were found to be statistically insignificant in driving entrepreneurial activity. These findings underscore the pivotal role of human capital development, particularly through skill acquisition, experience and education, in fostering entrepreneurship among returning migrants, as opposed to relying solely on financial aspects. This research contributes to the existing literature by elucidating the complex interplay between foreign employment, remittances, and entrepreneurial outcomes, thereby providing valuable insights for potential interventions to foster entrepreneurial activities.